The customer journey in the light of sensory marketing for fast food restaurants - Mohammed Edan Al Khazraje; Mustafa Raad Saleh; Noor Khaleel Ibrahem (Управленец)
Providing high-quality services and delivering a positive customer experience has become critical to the success of any restaurant. The purpose of the paper to analyse the customer journey during fast food service delivery, establish a correlation between sensory marketing and the customer journey, and improve the interaction with touchpoints by comprehending the sensory influences that can be used to enhance the customer experience throughout the journey. The theoretical basis of the study is comprised of classical marketing theory and the customer-centric approach. Structural equation modelling, descriptive statistics, regression and correlation analyses were used as research methods. The empirical framework includes the results of an online survey with 303 respondents, who are regular customers of four most popular fast food restaurants in Baghdad (Iraq). SPSS V.26 software was used to analyse and process the data. The study found that there is a significant relationship between sensory marketing and the customer journey. The fast-food restaurants use sensory marketing techniques (visual, auditory, olfactory, and gustative) to enhance the customer experience and better manage the customer's journey during food ordering. In the fast food industry, gustative and olfactory marketing techniques have the most significant impact on the customer journey. It was also revealed that the interaction with touchpoints is influenced by the sensory response of the customer.